Geosphere Phenomena from a Geographical Perspective: Examination of Substance and Complexity - Lasaiba, Mohammad Amin (Universitas Pattimura, 2022)
In the study of geography, the complexity studied covers a broad aspect of various geosphere phenomena with a unique approach as a geographical identity in examining every problem spread across the earth. The approach referred to as an analytical tool in assessing geographic reality includes spatial, ecological, and complex regional approaches. From this approach, geographers can examine various realities on earth more comprehensively by referring to the multiple problems in each region and simultaneously being a differentiator with various other sciences. From a geographical perspective, the geosphere phenomenon is analyzed based on the regional landscape as a causative factor. The underlying physical conditions are accompanied by various human activities that indirectly change nature so that the area experiences multiple damages. Spatially and ecologically, various damages can be mapped, emphasizing human interaction with nature. Then, it is thoroughly studied in a complex area so that an understanding of the causes of flooding and solutions that can be put forward can be realized more specifically. It is the geography specification that contributes ideas for advancing science and knowledge.